The Evaluation of Acute Pancreatitis into Acute Recurrent Pancreatitis in Children: The Impact of Etiological Factors - Kofla-Dlubacz, M.D., Ph.D., Anna; Jamer M.D., Tatiana; Akutko M.D., Ph.D., Katarzyna; Pytrus M.D., Ph.D., Tomasz; Iwańczak M.D., Ph.D., Barbara; Stawarski M.D., Ph.D., Prof. Andrzej (International Journal of Innovative Research in Medical Science, 2021)
Background: The incidence of acute pancreatitis (AP), acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) in pediatric population is rising and becomes common clinical problem in gastroenterology. The assessment of morbidity risk factors is necessary to improve the quality of diagnosis, to determine further treatment and to identify groups with poor prognosis of the evolution of AP into ARP and CP. Objectives: The assessment of etiological factors in acute and acute recurrent pancreatitis in children. Material and methods: From January 2015 to November 2017, data on etiological factors responsible for the onset of AP and ARP were collected in a group of pediatric patients hospitalized at the Department of Paediatrics, Gastroenterology and Nutrition, Medical University of Wroclaw, Poland. The study group consisted of 39 patients (27 patients with AP, 11 patients with ARP and 1 with CP). Results: The potential etiological factor was established in 85.2% of children with AP and in 100% of children with ARP. Mutations in the SPINK1 gene were found in 44.4% of children from the ARP group, no mutations in the PRSS1 gene were found in this group. In all patients with a genetic predisposition (SPINK1 mutation) during the first episode of the ARP, coexistence of an additional predisposing factor was found. Conclusions: Patients with ARP require diagnostics towards mutations predisposing to the transition of AP into a chronic disease. The interaction of additional triggers plays a role in the development of pancreatitic inflammatory disease in genetically predisposed individuals.